Incidência de sintomas depressivos em médicos residentes de primeiro ano e sua relação com características ocupacionais - Pires, Daniela Betinassi Parro [UNIFESP] (2009)
Objective: To study the depression symptoms f incidence of interns and its correlation with occupational characteristics, such as satisfaction/stress about their training program. Method: All interns from 2006 in a teaching hospital (N=166) were invited to participate in this prospective longitudinal study (T1= 1st week, and T2= 8th month of training). They answered the Beck Depression Inventory (BDI) and an occupational characteristics questionnaire. Results: 111 interns participated of the study (67% of the population), with median age of 25; 50.5% were female; 61.3% from clinical specialties. None of them scored for depression symptoms (BDI score.16) at T1, and 10 did at T2, with an increase (p<0.01) of the BDI median value from 2 to 5 (depressive symptoms f incidence of 9%). The BDI score at T2 was correlated with training satisfaction, difficulty with patients, and stressful relationships. The higher was the BDI score at T2, the lower was the satisfaction score with the training (p<0.01), specifically about satisfaction with the whole training, leisure time amount, health habits, and own performance; and the higher was the stress with colleagues f relationships. It was not found any correlations (p>0.05) among interns f BDI score and satisfaction with learning environment, stressful relationship with professors or nursing team, time spent with critically ill patients, giving bad news and number of hours on nightshifts. Conclusion: The interns were more affected by their relationship with colleagues than professors or by their difficulties in dealing with critically ill patients, what can be a proxy of the competitive feelings among them.